Social ecology of artisanal sand mining in the Niger River around Bamako, Mali - Katharina Salomea Hemmler; Bouraima Camara; Andreas Buerkert (PLoS ONE, 2025)
Sand, shaping both natural waterways and urban infrastructure, has recently seen a major surge in extraction, particularly in rapidly urbanizing regions like West Africa. To assess the organization, quantification, and socio-ecological implications of sand mining around Mali’s capital Bamako, we employed a mixed methods approach including structured and unstructured interviews, truck counts, turbidity analyses, and river depth measurements. Our study identified five artisanal systems for mining sand and gravel from the Niger River, using tied-up pirogues, single pirogues, carts, tractors, and trucks. Recent increases in extracted quantities, workforce size, and sand prices were observed, resulting in an estimated annual extraction of 4.86 million m3 in 2022, mainly sourced from upstream of Bamako. With extraction rates surpassing natural replenishment, the riverbed in the study communities of Gouni and Usine Toch has reportedly lowered by 1.4 m and 1.8 m during the last 50 years. Mining activities are highly informal, characterized by self-organization, low and irregular salaries, and unsafe working conditions, particularly for women. Economically, sand mining activities have created symbiotic relationships rather than conflicts with local farming, fishing and other livelihoods. Sand mining operations did not significantly affect the Niger River’s water turbidity, which varied primarily with seasonal rainfall fluctuations. Recent developments suggest that mining activities are accelerating, with mechanized practices likely to replace current artisanal methods and underlying social structures.